(untitled) (Genius Repository, 2023)
During the reproduction of experimental toxic hepatitis by administering heliotrine, it was found that the HIF-1 content averaged 0.101667±0.0022 ng/l. In blood plasma, the average HIF-1 values were 0.2136±0.0066 ng/l. After treatment in group I, HIF-1α indices were 0.317±0.022 (p <0.01), in group II – 0.404±0.031 (p≤0.02), in group III – 0.365±0.026 (p≤0.001), in group IV group – 0.421±0.028 (p≤0.001). During the reproduction of experimental toxic hepatitis by administering heliotrine, it was found that the ALT content was on average 25.93 ± 2.91 U/l, and the AST content was at the level of 22.23 ± 1.95 U/l. The de Rits number was 1.17±0.16. Direct bilirubin was at the level of 3.90±0.44 mmol/l, indirect bilirubin – 8.10±0.8 mmol/l. Total bilirubin was 12.01±1.16 mmol/l. Moreover, the OR (odds ratio) was 0.93219976. The 95% CI (confidence interval) was 0.88765239. χ 2= 0.9633286 (Wilkonson test). The MannWhinney test (U test) was 0.87219981 at p><0.05. Conclusions: The developed amino acid mixture is superior to traditional methods of treatment (Infezol) in terms of the effectiveness of influence on the development and course of experimental toxic hepatitis, which is proved by the study.>